2017
DOI: 10.1002/anie.201704921
|View full text |Cite
|
Sign up to set email alerts
|

Noncovalent Immobilization of Molecular Electrocatalysts for Chemical Synthesis: Efficient Electrochemical Alcohol Oxidation with a Pyrene–TEMPO Conjugate

Abstract: Electrocatalytic methods for organic synthesis could offer sustainable alternatives to traditional redox reactions, but strategies are needed to enhance the performance of molecular catalysts designed for this purpose. Herein, we describe the synthesis of a pyrene-tethered TEMPO derivative (TEMPO = 2,2,6,6-tetra-methylpiperidinyl-N-oxyl) that undergoes facile in situ non-covalent immobilization onto a carbon-cloth electrode. Cyclic voltammetry and controlled potential electrolysis studies demonstrate that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
94
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(100 citation statements)
references
References 81 publications
4
94
0
Order By: Relevance
“…In this report, we demonstrate the generation of ah ighly reactive thiourea radical by means of flavin photoelectrocatalysis and its application in the oxidation of unactivated alcohols. [9] The additive features granted by photoelectrochemistry proved critical, as neither photoredox catalysis nor electrocatalysis alone can provide the same reactivity in this catalytic system. Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
“…In this report, we demonstrate the generation of ah ighly reactive thiourea radical by means of flavin photoelectrocatalysis and its application in the oxidation of unactivated alcohols. [9] The additive features granted by photoelectrochemistry proved critical, as neither photoredox catalysis nor electrocatalysis alone can provide the same reactivity in this catalytic system. Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
“…Theb enzene ring Ar 1 of the biaryl oxime could be functionalized with an electronically diverse range of substituents at the position para or meta to the other phenyl group Ar 2 . When a meta-substituted substrate was used, the annulation occurred in ar egioselective manner at the site para to the functional group on Ar 1 because steric hindrance was mitigated (13)(14)(15)(16)(17)(18). In contrast, previously reported cyclizations that proceeded through sterically less hindered iminyl radical intermediates showed either reduced or no selectivity at all.…”
mentioning
confidence: 96%
“…Our first task was to identify optimal conditions for the cyclization of 1 (Table 1; Supporting Information, Tables S1 and S2). Initial screening revealed that the best reaction system consisted of (2,2,6,6-tetramethylpiperidin-1-yl)oxyl (TEMPO;5 mol %) [15] and KOH( 0.5 equiv) in am ixed solvent of MeCN/H 2 O( 1:1). Notably,K OH fulfilled ad ual role of base and supporting electrolyte,which eliminated the need for additional salt.…”
mentioning
confidence: 99%
“…Despite such efforts, the immobilization of molecular organometallic electrocatalysts through modification of their ligand molecules cannot avoid degradation of catalytic activity. This can be attributed to (1) the degradation of catalytic activity after the introduction of functional groups, leading to changes in electron distribution and energetics in electrocatalysts,, , and (2) the vulnerability of ester linkages to hydrolytic degradation, resulting in detachment of electrocatalysts from photoelectrodes , . It is well‐known that the introduction of electron withdrawing and donating groups has a significant effect on their redox potentials and catalytic activity , , .…”
Section: Immobilization Of Molecular Electrocatalysts By Covalent mentioning
confidence: 99%